Market Risk Disclosure: A Study on Systemic Banks in Indonesia - Hendri Setyawan; Edy Suprianto (Yayasan Ilomata, 2022)
This study was conducted to determine the extent to which the disclosure of market risk, especially the risk of the market carried out by banks in Indonesia. Observation of the disclosure in this study using method by Scannella and Polizzi (2018) which carried out quantitative and qualitative assessment. This study focuses on four banks in Indonesia that have a systemic impact and have Islamic subsidiaries. The year of observation is for three years from 2018 to 2020. The results showed that that in general using checklist provided by Scannella and Polizzi, (2018) the results show insufficient image of market risk disclosure among Indonesian large banks. For instance, graphical information about Value at Risk (VaR), back testing, and also stress testing. Furthermore, information about expected shortfall need to be more expanded.